Synthesis of benzofuran-6-carboxylic acid, an intermediate of lifitegrast with low-carbon footprints - Zade, Vishal M.; Athawale, Paresh R.; Kopperi, Harishankar; Mohan, S. Venkata; Reddy, D. Srinivasa (ACS SUSTAINABLE CHEMISTRY & ENGINEERING, 2024)
Keywords: benzofuran-6-carboxylicacid; dry eye disease; life cycle; lifitegrast; process development

Scalable and sustainable reductive amidation of nitroarenes, nitroalkenes, and nitroalkyls with acyl saccharins in aqueous media - Khamkar, Sunil L.; Mohan, Rayala; Santhosh, J.; Shinde, Harish M.; Handore, Kishor L.; Mohan, S. Venkata; Reddy, D. Srinivasa (Communications Chemistry, 2025)
Amide bond formation is essential in both organic and medicinal chemistry, however, most existing methods present poor ecological efficiency. Here, we report a scalable and sustainable method for synthesizing N-substituted amides from nitroarenes, nitroalkenes, nitroalkyls, and acyl saccharin in aqueous media. This atom-efficient approach avoids column chromatography, offers high yield, and is compatible with various functional groups. It is applicable to synthesize Dispyrin, a bromopyrrole alkaloid, amide-based drugs, and agrochemicals, including paracetamol, with solvent and saccharin recycling. A comprehensive Life Cycle Assessment (LCA; ISO 14044) was conducted to evaluate the environmental impacts and sustainability of nine Active Pharmaceutical Ingredients (APIs) produced via Amidation Route (AR) and Saccharin Amidation Route (SAR). The study shows SAR methods reduce carbon footprints and environmental impacts compared to AR methods, being carbon-negative and resource-efficient. Additional reductions can be achieved through saccharin recycling and the integration of renewable energy sources, demonstrating saccharin-based processes potential to minimize environmental burdens in pharmaceutical synthesis.